Formes dynamiques: Le geste sculptural et le principe de la variation (Signifiances (Signifying), 2021)
AbstractIn a dialogue between phenomenology and semiotics, anthropology and the theory of establishment, this article examines the becoming and the dynamics of forms, captured either in their succession or in their co-presence. The analysis of Tony Cragg's preparatory drawings allows us to highlight the trace, in relation to expression or expressiveness and a logic that is no longer representative, but presentational. It is then a question of distinguishing personal or impersonal instances of enunciation (participant, subjectal and subjective), but also of thinking about the interaction with materials and taking into consideration the determinations by a social and cultural environment (doxical representations, normativizations), between “instituent” re-expression and the invention of new possibilities.  Keywords : enunciation instances ; formation ; trace ; preparatory drawings ; variant